Rancang Bangun Sistem Kendali Operasional Boiler Berbasis Web Data Logger LAN dan PLC Pada PT. XYZ - Taufik Ridwan (Jurnal Teknik Elektro, 2017)
This research aims to design a monitoring and control system architecture operations previously conventionalboiler into remote access using a data logger applications as data acquisition, using a corporate LAN networkas communication’s media and PLC (Programmable Logic Controller) as the control brain. This research isrealized by making the control circuit, and configuration of hardware devices and software related web datalogger system. Design process is done with the installation of the supporting device, the manufacture of panels,mounting transducer which serves as input monitoring and modulating control. This design is applied to theboiler at one plant which is controlled by the PLC, while web data logger that will monitor and store alloperational activities and processes that occur. Data can be accessed using a computer (server) that is connectedto a LAN network that allows multiple computers (client) that connects the same LAN network can performoperations such as on the server’s computer using the VNC viewer software application. The results show thedesign of the boiler activity can be monitored and controlled from a computer with the apperance in the form oftables and charts, while data storage results in a CSV file fomat.Keywords: Boiler, Web Data Logger, PLC, LAN Communication, CSV File.